Zara-- y sus hermanas - Badía, Enrique (LID, 2008)
Enrique Badía revela las claves de la creación por Amancio Ortega del líder mundial del mercado de moda. Con prólogo de Carlos Rodríguez Braun.
Date of publication from resource description page (Safari, viewed February 25, 2014). - "Emprendedores mundiales.". - Includes bibliographical references. - Online resource; title from cover (Safari, viewed February 25, 2014)
Keywords: Ortega Gaona, Amancio -- 1936-; Zara Ltd; Fashion merchandising -- Case studies; Ortega Gaona, Amancio; 1936-; Mode; Marchandisage; Études de cas; Fashion merchandising; Case studies